Globalization and the politics of development in the Middle East - Henry, Clement M., 1937-; Springborg, Robert (New York : Cambridge University Press, 2010)
'In a new edition of their book on the economic development of the Middle East and North Africa, Clement Henry and Robert Springborg reflect on what has happened to the region's economy since 2001. How have the various countries in the Middle East responded to the challenges of globalization and to the rise of political Islam, and what changes, for better or for worse, have occurred? Utilizing the country categories they applied in the previous book and further elaborating the significance of the structural power of capital and Islamic finance, they demonstrate how over the past decade the monarchies (as exemplified by Jordan, Morocco, and those of the Gulf Cooperation Council) and the conditional democracies (Israel, Turkey, and Lebanon) continue to do better than the military dictatorships or'bullies' (Egypt, Tunisia, and now Iran) and'the bunker states' (Algeria, Iraq, Libya, Sudan, Syria, and Yemen)'--
'Books published in The Contemporary Middle East series address the major political, economic and social debates facing the region today. Each title comprises a survey of the available literature against the background of the author's own critical interpretation which is designed to challenge and encourage independent analysis. While the focus of the series is the Middle East and North Africa, books are presented as aspects of the rounded treatment, which cut across disciplinary and geographic boundaries. They are intended to initiate debate in the classroom, and to foster understanding amongst professionals and policy-makers'--
Machine generated contents note: 1. The globalization dialectic; 2. The challenges of globalization; 3. Political capacities and local capital; 4. Bunker state; 5. Bully praetorian states; 6. Globalization monarchies; 7. Precarious democracies; 8. Conclusion.
Keywords: Globalization; Middle East -- Economic conditions -- 1979-; Middle East -- Politics and government -- 1979-